Are Schools in Prison Worth It? The Effects and Economic Returns of Prison Education - Stickle, Benjamin F. (American journal of criminal justice, 2023)
Recent expansions in prison school offerings and the re-introduction of the Second Chance Pell Grant have heightened the need for a better understanding of the effectiveness of prison education programs on policy-relevant outcomes. We estimate the effects of various forms of prison education on recidivism, post-release employment, and post-release wages. Using a sample of 152 estimates drawn from 79 papers, we conducted a meta-analysis to estimate the effect of four forms of prison education (adult basic education, secondary, vocational, and college). We find that prison education decreases recidivism and increases post-release employment and wages. The largest effects are experienced by prisoners participating in vocational or college education programs. We also calculate the economic returns on educational investment for prisons and prisoners. We find that each form of education yields large, positive returns due primarily to the high costs of incarceration and, therefore, high benefits to crime avoidance. The returns vary across education types, with vocational education having the highest return per dollar spent (USD3.05) and college having the highest positive impact per student participating (USD16,908).